Hubungan Gratitude dan Subjective Well-Being Odapus Wanita Dewasa Awal di Syamsi Dhuha Foundation Bandung - Nadia Felicia Mahardhika; Lilim Halimah (Psympathic : Jurnal Ilmiah Psikologi, 2017)
Systemic Lupus Erythematosus is a chronic illness, in which 90% of the sufferers are early adult women. They faced many difficulties which can cause depressions. People with lupus in Syamsi Dhuha Foundation show high positive affect and said that they satisfied with their lives. This research is a population research to 30 people with lupus in Syamsi Dhuha Foundation, using correlational technique. The goal is to examine the correlation between gratitude and subjective well-being of early adult women with lupus at Syamsi Dhuha Foundation. The instrument for gratitude is GRAT-R (Watkins, 2002) and for subjective well-being are SPANE (Diener, 2012), SWLS (Diener, 1987), and Domain Satisfaction Scales (Public Attitudes and Behaviours towards the Environment Omnibus Survey, 2007). The results are: 1) Strong positive correlation between gratitude and subjective well-being; 2) Twenty seven subjects who show high gratitude; and 3) Twenty one subjects report high subjective well-being.